How and why to be human milk donor? A descriptive study - Cynara Gurgel Pereira; Maria Vera Lúcia Moreira Leitão cardoso; Grazielle Roberta Freitas da Silva; Maria Gorette Andrade Bezerra (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
It is a research developed at a Human Milk Bank to inquire as the mother givers had become Human Milk (HM) giver of a Human Milk Bank(HMB). To identify, according to these, which the reasons that had stimulated them to be givers.Qualitative research through a HMB in a maternity of great transport of Fortaleza-Ce in 2005. The collection of the data consisted of structuralized interview does not contend given of identification and two questions with 24 givers of HM through the domiciliary visit. The organization of the data was in Bardin (2004) through subjects and categories. After deep readings we extract the meaning of you say them. The subjects and categories that more importance were had been respectively "Use of informative resources" and "Written Communication". Already the subjects and categories that had had little importance had been: "Situational adequacy" and "Visit to the Milk Bank.One concludes that the distribution of folders informative was to the way most common to become givers, the telephone used in the cadastre of the donation, and the milk excess was the first reason that had taken them the donation.